FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PELATIHAN SERTA DAMPAKNYA PADA KINERJA PEGAWAI (STUDI KASUS PADA PEJABAT ESELON IV DILINGKUNGAN PEMERINTAH DAERAH ACEH) - Andri Sufianzah; Nasir Nasir; Said Musnadi (Jurnal Magister Manajemen, 2018)
This study aims to determine the training effectiveness as well as its impact on the performance of civil servants within Aceh government. The predictor variable for the training effectiveness consists of the trainer competency, training environment, and co-workers support. The sample of the study are 148 civil servants attending the level four leadership training. The empirical data was collected by using questionnaire and then the data analyzed by the structural equation model. The study found that trainer competency, training environment and co-workers support have a positive and significant effect on the effectiveness of level four leadership training. The Co-workers and the training effectiveness have a positive and significant effect on employee performance. The training effectiveness has mediating the effect of trainer competency, training environment and co-workers support on employee performance. The mediating effect appearing by the training effectiveness as intervening variable between co-workers support and employee performance is partial mediation